1996
DOI: 10.1088/0031-8949/53/3/012
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of laser-produced carbon plasma

Abstract: Carbon plasmas produced by radiation from a ruby laser (wavelength 694.3 nm) focussed onto a carbon target in vacuum are studied spectroscopically with a time resolution of 40 ns. Measured line profiles of several ionic species (CI-CIV) were used to infer electron density and temperature at several positions above the target surface as function of time elapsed after the beginning of the laser pulse. The particle density at several positions above the target surface as function of time was judged from corrected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…With increasing distance from the target the electron temperature falls from 2.43 eV at 1 mm to 1.6 eV at 11 mm while the electron density decreases from 2.5×10 17 cm −3 at 1 mm to 1 × 10 17 cm −3 at 11 mm. These results are consistent with recently reported values of such quantities [27,28]. The variation of electron temperature and density with distance (z) perpendicular to the target surface shows a z −0.1 and z −1 dependence respectively [29].…”
Section: Resultssupporting
confidence: 92%
“…With increasing distance from the target the electron temperature falls from 2.43 eV at 1 mm to 1.6 eV at 11 mm while the electron density decreases from 2.5×10 17 cm −3 at 1 mm to 1 × 10 17 cm −3 at 11 mm. These results are consistent with recently reported values of such quantities [27,28]. The variation of electron temperature and density with distance (z) perpendicular to the target surface shows a z −0.1 and z −1 dependence respectively [29].…”
Section: Resultssupporting
confidence: 92%
“…In the scope of this model one generally finds that the maximum plasma temperature directly above the target surface (in the so-called Knudsen layer) is equal to, or slightly larger than, T TOF and the maximum temperature in the expanding plasma cloud itself is a few times smaller. Our earlier experimental results [11] have already shown that there is reasonable agreement between the experimentally determined plasma parameters and the predictions of the effusion model. Because the effusion model is a one-dimensional model, it does not account for the lateral expansion of the plasma cloud, so the calculated temperature and density values are higher than the actual ones.…”
Section: Discussionsupporting
confidence: 74%
“…The temperature of the particles leaving the Knudsen layer (T KL ) is given first. We have chosen to reproduce the maximum density of the expanding plasma cloud at the time that corresponds to the observed time of flight [11]. We can see that it corresponds quite well to the observed T TOF .…”
Section: Discussionmentioning
confidence: 92%
“…These results are consistent with the recently reported values of such quantities. 31,32 The variation of electron temperature with distance ͑z͒ perpendicular to the target surface shows a z Ϫ0.1 dependence. For these studies time integrated intensities were used and the value of T e presented at different distances from the target should be regarded as indicative of the average conditions occurring in an Nd:YAG laser induced carbon plasma, rather than defining the conditions at a particular stage of its evolution.…”
Section: A Spatial Dependencementioning
confidence: 99%